Combined Flexural and Shear Strengthening of RC T-Beams with FRP and TRM: Experimental Study and Parametric Finite Element Analyses - Daniel A. Pohoryles (MDPI AG, 2021)
Due to inadequacies of reinforcement design in older structures and changes in building codes, but also the change of building use in existing structures, reinforced concrete (RC) beams often require upgrading during building renovation. The combined shear and flexural strengthening with composite materials, fibre-reinforced polymer sheets (FRP) and textile reinforced mortars (TRM), is assessed in this study. An experimental campaign on twelve half-scale retrofitted RC beams is presented, looking at various parameters of interest, including the effect of the steel reinforcement ratio on the retrofit effectiveness, the amount of composite material used for strengthening and the effect of the shear span, as well as the difference in effectiveness of FRP and TRM in strengthening RC beams. Significant effects on the shear capacity of composite retrofitted beams are observed for all studied parameters. The experimental study is used as a basis for developing a detailed finite element (FE) model for RC beams strengthened with FRP. The results of the FE model are compared to the experimental results and used to design a parametric study to further study the effect of the investigated parameters on the retrofit effectiveness.